Voluntary work and wages - Bruna Bruno; Damiano Fiorillo (Economics and Econometrics Research Institute (EERI), 2014)
The effects of voluntary work on earnings have recently been studied for some developed countries such as Canada, France and Austria. This paper extends this line of research to Italy, using data from the European Union Statistics on Income and Living Conditions (EU-SILC) dataset. A double methodological approach is used in order to control for unobserved heterogeneity: Heckman and IV methods are employed to account for unobserved worker heterogeneity and endogeneity bias. Empirical results show that, when the unobserved heterogeneity is taken into account, a wage premium of 2.7 percent emerges, quite small if compared to previous investigations on Canada and Austria. The investigation into the channels of influence of volunteering on wages gives support to the hypotheses that volunteering enables the access to fruitful informal networks, avoids the human capital deterioration and provides a signal for intrinsically motivated individuals.
Keywords: C31; C36; J31; 330; Voluntary work; wages; Mincer equation; selection bias; instrumental variables; Italy